2008
DOI: 10.1021/ol801616s
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Catalyzed Enantioselective Tandem Alkylation/Arylation of Primary Phosphines. Asymmetric Synthesis of P-Stereogenic 1-Phosphaacenaphthenes

Abstract: Enantioselective tandem alkylation/arylation of primary phosphines with 1-bromo-8-chloromethylnaphthalene catalyzed by Pt(DuPhos) complexes gave P-stereogenic 1-phosphaacenaphthenes (AcePhos) in up to 74% ee. Diastereoselective formation of four P-C bonds in one pot with bis(primary) phosphines gave C2-symmetric diphosphines, including the o-phenylene derivative DuAcePhos, for which the rac isomer was formed with high enantioselectivity. These reactions, which appear to proceed via an unusual metal-mediated nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 29 publications
2
62
0
Order By: Relevance
“…As expected, a mechanistic study suggested that the major enantiomer of product was formed from the major diastereomer of the platinum–phosphido intermediate [63]. Glueck and co-workers also developed an analogous method for the tandem alkylation/arylation of primary phosphines on the basis of a platinum catalyst resulting in several enantio-enriched phosphaacenaphtalenes [64]. …”
Section: Reviewmentioning
confidence: 96%
“…As expected, a mechanistic study suggested that the major enantiomer of product was formed from the major diastereomer of the platinum–phosphido intermediate [63]. Glueck and co-workers also developed an analogous method for the tandem alkylation/arylation of primary phosphines on the basis of a platinum catalyst resulting in several enantio-enriched phosphaacenaphtalenes [64]. …”
Section: Reviewmentioning
confidence: 96%
“…Ligands possessing phosphorus and carbon atoms in the peripositions of the naphthalene ring generally act as monodentate via phosphorus [64,65]. An exception to this is an organometallic species 90, which is obtained by the elimination of methane on coordination of [CoMe(PMe 3 ) 4 ] to 89 (Scheme 39) [66].…”
Section: Nappc Ligands and Complexesmentioning
confidence: 99%
“…In this series, only DuPhos has been applied in platinum complexes [18][19][20]. 3-Diphenylphosphino-1-phenyl-1,2,3,6-tetrahydrophosphinine and its 1,2,3,4,5,6-hexahydrophosphinine derivative were also described as novel bidentate P-ligands in Pt(II) complexes [21][22][23][24][25][26] showing unusual regioselectivity as catalysts in the hydroformylation of styrene [27].…”
Section: Introductionmentioning
confidence: 99%